Answer:
101
Step-by-step explanation:
h(t)= -20+11t
h(11)= -20+11(11)
h(11)= -20+121
h(11) = 101
Answer & Step-by-step explanation:
In the problem, we are given an equation. h(t) = -20 + 11t
In the equation, t represents an unknown value. So, if we are given a number that is in the replacement of t, then we can plug that number in to where t is at.
t = 11
h(11) = -20 + 11(11)
h(11) = -20 + 121
So, h(11) is equal to 101
x=4
-4+3x=8
+4 +4
<u>3x</u>=<u>12</u>
3x 3x
−234.96
Hope its the right answer that you're looking for :)